Islam Through Western Eyes: From the Crusades to the War on Terrorism - JONATHAN LYONS (Columbia University Press, 2012)
the terrorist attacks of September 11, 2001, and their aftermath are just the latest reminder of the Westâ€™s complete and enduring failure to engage in any meaningful and productive way with the world of Islam. For almost ten centuries, attempts at understanding have been held hostage to a grand, totalizing Western narrative that shapes what can and, more important, what cannot be said and thought about Islam and the Muslims. This is no less true today, from the political arena to the counterterrorism think tanks, from the academy to the Internet â€œblogosphere,â€ than it was in the medieval halls of the Roman Curia and the courts of the European Crusaders. Further, this same narrative, which reflects what I call the anti-Islam discourse, exercises a profound and corrosive effect on a range of issues across the contemporary social sciences, including sociology, politics, the history of ideas, law, religion, international relations, human rights, and security studies. It casts a shadow over the way social scientists of various stripes think and write and speak about Islam and the Muslims. It shapes how social scientists listen to what Muslims say and interpret what they do. And it guides their research programs and publications, their private advice to governments,and their statements to the press and the public at large. These developments have, in turn, left Western societies both intellectually unprepared and politically unable to respond successfully to some of the most significant challenges of the early twenty-first centuryâ€”the global rise of Islamist political power, the more narrow emergence of religious violence and terrorism, clashes between established social values and multicultural rights on the part of growing Muslim immigrant populations, and so on.